Adaptive T cell responses induced by oncolytic Herpes Simplex Virus-granulocyte macrophage-colony-stimulating factor therapy expanded by dendritic cell and cytokine-induced killer cell adoptive therapy. (3rd April 2017) - Ren, Jun; Gwin, William R.; Zhou, Xinna; Wang, Xiaoli; Huang, Hongyan; Jiang, Ni; Zhou, Lei; Agarwal, Pankaj; Hobeika, Amy; Crosby, Erika; Hartman, Zachary C.; Morse, Michael A.; et al.
ABSTRACT: Purpose : Although local oncolytic viral therapy (OVT) may enhance tumor lysis, antigen release, and adaptive immune responses, systemic antitumor responses post-therapy are limited. Adoptive immunotherapy with autologous dendritic cells (DC) and cytokine-induced killer cells (DC–CIK) synergizes with systemic therapies. We hypothesized that OVT with Herpes Simplex Virus-granulocyte macrophage-colony-stimulating factor (HSV-GM-CSF) would induce adaptive T cell responses that could be expanded systemically with sequential DC–CIK therapy. Patients and Methods : We performed a pilot study of intratumoral HSV-GM-CSF OVT followed by autologous DC–CIK cell therapy. In addition to safety and clinical endpoints, we monitored adaptive T cell responses by quantifying T cell receptor (TCR) populations in pre-oncolytic therapy, post-oncolytic therapy, and after DC–CIK therapy. Results : Nine patients with advanced malignancy were treated with OVT (OrienX010), of whom seven experienced stable disease (SD). Five of the OVT treated patients underwent leukapheresis, generation, and delivery of DC–CIKs, and two had SD, whereas three progressed. T cell receptor sequencing of TCR β sequences one month after OVT therapy demonstrates a dynamic TCR repertoire in response to OVT therapy in the majority of patients with the systematic expansion of multiple T cell clone populations following DC–CIK therapy. This treatment was well tolerated and long-term event free and overall survival was observed in six of the nine patients. Conclusions : Strategies inducing the local activation of tumor-specific immune responses can be combined with adoptive cellular therapies to expand the adaptive T cell responses systemically and further studies are warranted.